Analisis Gaya Belajar Siswa Kelas VI MI Al-Zaytun, Sandrem, Kecamatan Gantar, Kabupaten Indramayu - Ita Sari; Anjar Sulistyani (SALAM: Jurnal Sosial dan Budaya Syar-i, 2022)
Student learning styles are very diverse. Teachers must have knowledge and skills in teaching. Teachers must recognize the characteristics of students in the delivery of learning. This study aims to determine the learning styles of 6th grade students at MI Al-Zaytun, Mekarjaya Village, Gantar District, Indramayu. The results showed that each student has a different learning style, so that in one class there are various learning styles as well. Visual style is learning style using sight, audiotorial learning style is learning style using hearing, kinesthetic learning style is using movement. In class 6 B 01 is more dominant to visual learning style as much as 37%, class 6 B 02 is more dominant to visual learning style as much as 36%, class 6 B 03 is more dominant to visual learning style 36%, class 6 B 04 is more dominant to visual learning style 35% visual learning, class 6 B05 is more dominant to Visual learning style 35%, class 6 B 06 is more dominant to Auditorial learning style 34%, class B 07 is more dominant to audiotorial learning style as much as 36%, class 6 B 08 is more dominant to kinesthetic learning style as much as 36%. By knowing the learning styles of students, it can make it easier for teachers to learn with students, make it easier for students to catch lessons and increase students' enthusiasm for learning.Keywords: Visual Learning Style; Auditory Learning Style; Kinesthetic Learning Style AbstrakGaya belajar siswa sangat beragam. Guru harus memiliki pengetahuan dan keterampilan dalam mengajar. Guru harus mengenali karakteristik peserta didik dalam penyampaian pembelajaran. Penelitian ini bertujuan untuk mengetahui gaya belajar siswa kelas 6 MI Al- Zaytun, Desa Mekarjaya, Kecamatan Gantar, Indramayu. Hasil penelitian ini setiap siswa memiliki gaya belajar yang berbeda sehingga dalam satu kelas terdapat bermacam gaya belajar pula. Gaya visual merupakan gaya belajar menggunakan penglihatan, gaya belajar audiotorial merupakan gaya belajar menggunakan pendengaran, gaya belajar kinestetik menggunakan gerakan. Pada kelas 6 B 01 lebih dominan kepada gaya belajar visual  sebanyak 37 %, kelas 6 B 02 lebih dominan kepada gaya belajar visual sebanyak 36 %, kelas 6 B 03 lebih dominan kepada gaya belajar visual 36%, kelas 6 B 04 lebih dominan kepada gaya belajar visual 35 %, kelas 6 B05 lebih dominan kepada gaya belajar Visual  35 %, kelas 6 B 06 lebih dominan kepada gaya belajar Auditorial 34 %, kelas B 07 lebih dominan kepada gaya belajar audiotorial sebanyak 36 %, kelas 6 B 08 lebih dominan kepada gaya belajar kinestetik sebanyak 36%. Dengan mengetahui gaya belajar yang dimiliki siswa, dapat memudahkan guru dalam pembelajaran dengan siswa, memudahkan siswa dalam menangkap pelajaran serta meningkatkan semangat belajar siswa.Kata kunci: Gaya Belajar Visual; Gaya Belajar Auditorial; Gaya Belajar Kinestetik